Aptamer-functionalized exosomes from bone marrow stromal cells target bone to promote bone regeneration. Issue 43 (29th October 2019) - Luo, Zhong-Wei; Li, Fu-Xing-Zi; Liu, Yi-Wei; Rao, Shan-Shan; Yin, Hao; Huang, Jie; Chen, Chun-Yuan; Hu, Yin; Zhang, Yan; Tan, Yi-Juan; Yuan, Ling-Qing; Chen, Tuan-Hui; et al.
Abstract : A novel strategy to deliver therapeutic exosomes to bone is developed for the first time by conjugating a specific BMSC-targeting aptamer to the exosomal surface. Abstract : In elderly people particularly in postmenopausal women, inadequate bone formation by osteoblasts originating from bone marrow mesenchymal stem cells (BMSCs) for compensation of bone resorption by osteoclasts is a major reason for osteoporosis. Enhancing osteoblastic differentiation of BMSCs is a feasible therapeutic strategy for osteoporosis. Here, bone marrow stromal cell (ST)-derived exosomes (STExos) are found to remarkably enhance osteoblastic differentiation of BMSCs in vitro . However, intravenous injection of STExos is inefficient in ameliorating osteoporotic phenotypes in an ovariectomy (OVX)-induced postmenopausal osteoporosis mouse model, which may be because STExos are predominantly accumulated in the liver and lungs, but not in bone. Hereby, the STExo surface is conjugated with a BMSC-specific aptamer, which delivers STExos into BMSCs within bone marrow. Intravenous injection of the STExo-Aptamer complex enhances bone mass in OVX mice and accelerates bone healing in a femur fracture mouse model. These results demonstrate the efficiency of BMSC-specific aptamer-functionalized STExos in targeting bone to promote bone regeneration, providing a novel promising approach for the treatment of osteoporosis and fracture.